2014
DOI: 10.1155/2014/921954
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Prenyl Group in the Activities of Osthole in Enhancing Bone Formation and Inhibiting Bone ResorptionIn Vitro

Abstract: Osteoporosis treatment always aimed at keeping the balance of bone formation and bone resorption. Recently, prenyl group in natural products has been proposed as an active group to enhance the osteogenesis process. Osthole has both the prenyl group and bone-protective activities, but the relationship is still unknown. In this study we found that osthole exerted a potent ability to promote proliferation and osteogenic function of rat bone marrow stromal cells and osteoblasts, including improved cell viability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
3
22
1
Order By: Relevance
“…OCN is also used as a biomarker of skeletal development, and increased serum OCN level is associated with increased bone mineral density during osteoporosis treatment [48,49]. However, in our study, elevated OCN levels were accompanied by decreased BMD.…”
Section: Discussioncontrasting
confidence: 66%
“…OCN is also used as a biomarker of skeletal development, and increased serum OCN level is associated with increased bone mineral density during osteoporosis treatment [48,49]. However, in our study, elevated OCN levels were accompanied by decreased BMD.…”
Section: Discussioncontrasting
confidence: 66%
“…The altered serum levels of CTX and osteocalcin were significantly reversed by treatment with mollugin. The activities of TRAP (marker for bone resorption) and ALP in osteoblasts are significantly altered in osteoporosis [15]. In this study, treatment with mollugin significantly reversed the altered activities of TRAP and ALP in osteoporotic rats.…”
Section: Discussionmentioning
confidence: 49%
“…30) Studies also showed that osthole attenuated intestinal, myocardial, and spinal cord ischemia-reperfusion injury in animal models. 31,32) Besides, osthole could effectively inhibit TGF-β1 expression in fibroblasts and protect against cardiac and hepatic fibrosis.…”
Section: )mentioning
confidence: 99%